Vocational interests 18 years after college - Strong, Edward K. (Edward Kellogg), 1884-1963 (University of Minnesota Press, 1955)
Vocational Interests 18 Years After College was first published in 1955. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. A pioneer in scientific vocational counseling, Edward K. Strong, Jr., devised the Strong Vocational Interest Blank some years ago as a tool to help the counselor find out what kind of work a young person is best suited for. In this volume Mr. Strong reports on a study which he undertook to determine the validity of the interest blank in predicting the future vocations of individuals. For this study, the interest scores of several hundred former college students were compared with the occupations in which these men were engaged 18 years later. The results provide answers to basic questions regarding the use of interest scores in vocational counseling. The findings also serve to confirm or modify the conclusions published earlier by Mr. Strong in his book Vocational Interests in Men and Women (a volume for which he was awarded the Butler Silver Medal by Columbia University). The original group whim the present study is based consisted of 884 Stanford University graduates whose interests had been revealed by the use of the Vocational Interest Blank while they were in college. Follow-up data on their actual careers are presented and analyzed for approximately three fourths of this number, the remainder being eliminated because they were engaged in occupations for which no specific scales were available. In addition to revising and amplifying Mr. Strong's earlier work on the subject, this volume outlines a number of developments which provoke new problems and point the way for future research.
Keywords: Stanford University -- Alumni and alumnae.; Stanford University; Vocational interests.; Intérêts professionnels.; 85.64 occupations.; PSYCHOLOGY -- Research & Methodology.; Universities and colleges -- Alumni and alumnae; Vocational interests